Family- work conflicts, work family sinergy, commitment organization, and job performance: survey in kupang city - Mariano Firmansyah; Selfiana Goetha (Jurnal Mantik, 2023)
This study aims to see the picture and influence of Family-Work Conflicts, Work Family Sinergy, and Organization Commitment on Job Performance in Kupang City, East Nusa Tenggara Province. The population in the study was office workers who were already married and had children. The sample in this study amounted to 200 respondents who were willing to answer 22 statements on the questionnaire through google form.  The sampling technique uses purposive sampling. The data analysis used is the analysis of SEM (Stuctural Equation Model) Partial Least Square (PLS) causality using Smart PLS 3.0 software. The results of statistical testing show that the variables Work family Synergy and Comitment Organization have a positive and significant effect on the variable Job Performance. This result is different from the Family-Work Conflicts variable which has a negative and insignificant influence on the Job Performance variable. Future research is expected to develop variables such as Job Stress, personality, Job Burnout and Mental Health. and can calcify more specific research objects such as field workers, part-time workers, single parents and shift workers to be able to compare the findings.